Butterfly-like enantiomerically homochiral CoII6CoIII4 clusters exhibiting both slow magnetic relaxation and ferroelectric property - Li, Qipeng (2014)
A pair of enantiomerically homochiral CoII6CoIII4 clusters featuring a butterfly-like structure, [CoII6CoIII4(μ3-OH)(μ3-X)(S-pa)4(pdm)6(pdmH)2](ClO4)4·3.5H2O (S-1) and [CoII6CoIII4(μ3-OH)(μ3-X)(R-pa)4(pdm)6(pdmH)2](ClO4)4·3.5H2O (R-1) (X = OH or OMe, S- or R-paH = S- or R-phenylalaninol and pdmH2 = pyridine-2,6-diyldimethanol), have been synthesized and structurally characterized. They are the second largest homochiral Co clusters constructed by chiral ligands. They are also the first example of high-nuclearity homochiral Co clusters having both slow magnetic relaxation behaviour and ferroelectric property.